Extreme stretching of high G:D ratio carbon nanotube fibers using super-acid. (November 2019) - Bulmer, John S.; Mizen, Jenifer E.; Gspann, Thurid S.; Kaniyoor, Adarsh; Ryley, James B.; Kiley, Patrick J.; Sparkes, Martin R.; O'Neill, Bill; Elliott, James A.
Abstract: Few-wall carbon nanotube (CNT) textiles with unparalleled graphitic perfection and a solitary, prominent radial breathing mode (RBM) associated with metallic chirality have been mechanically stretched in chlorosulfonic acid (CSA) to a degree so far unseen in CNT textiles (150–250% of original length) with notably little tension required. This dramatically enhanced their microstructural alignment and density and, after most of the residual CSA was removed by a vacuum bake, the de-doped fiber's electrical conductivity was found to be 45% greater than single-crystal graphite – a significant milestone for CNT conductor development towards graphitic intercalation compounds (GICs) and traditional metals. Correlation tables and validated, multivariate statistical models show that conductivity is overwhelmingly linked to stretching degree, although eventually saturates near single-crystal graphite levels, implying the existence of a maximum undoped conductivity. The degree of stretching within CSA is correlated with the original mechanical properties (tenacity, elongation-to-break, and linear density); the Raman G':G ratio and the upper-end oxidation temperature in thermogravimetric analysis also predict the best results. Less graphenically pristine CNT materials stretch to a lower degree in CSA, similar to previous reports. This study highlights the importance of post-synthesis processing to achieve superior performance in carbon nanotube textile materials. Graphical abstract: Image 1